The Social Standing versus the Mind Standing of Older Adults in Egypt: Cross-sectional Analysis of the Relationship Between Social Capital and Cognitive Functions - Shinaishen, Shaza H, Dr (AUC Knowledge Fountain, 2025)
Introduction: Egypt's population, much like that of other countries, is expected to age considerably over the course of the coming decades. Although biological and socioeconomic predictors of cognitive function have been studied widely, personal level social capital remains unexplored, especially in LMICs. Purpose: This study primarily investigates the relationship between individual social capital and cognitive functioning among older adults aged 65 years and older in Egypt using the structural and cognitive components of social capital, including group membership, civic engagements, and caregiving roles. Methods: A cross-sectional survey on 363 older individuals in different geographical and demographic segments of Egypt using proportionate stratified sampling. Cognitive function was assessed using culturally adapted m-ACE tool, while individual-level social capital was assessed by SASCAT through a face-to-face interviewing method. Results: Several aspects of individual social capital were significantly associated with cognitive function. Group membership (p =0.010), civic engagement (p < 0.001), and caregiving responsibility (p < 0.001) were all positively associated with m-ACE scores, irrespective of their socioeconomic status (SES) and other demographic factors. However, age and education level significantly predicted cognitive outcomes. Social capital has retained a strong independent effect on cognitive performance while considering SES and other covariates. Conclusions: Individual social capital significantly increases cognitive health in older Egyptians. Evidence from this study can serve as support for designing inclusive, age-friendly policies and practices that create civic participation, social inclusion, and community engagement for older persons, among other areas. Accordingly, there is a pressing need for culturally informed measurement tools, tailored to LMIC environments. Moreover, the social determinants of cognitive aging need to be integrated into sustainable aging policies in Egypt and similar context countries.